2021
DOI: 10.4103/jmas.jmas_106_21
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided thoracal paravertebral block for awake thoracoscopic lobectomy in a high-risk patient

Abstract: One-lung ventilation provided by double-lumen tube intubation under general anaesthesia has conventionally been considered necessary for thoracoscopic major pulmonary resections. Recently, regional anaesthesia techniques have been used to avoid complications of tracheal intubation and general anaesthesia. Although paravertebral block (PVB) comes to the fore as a safe and useful regional anaesthesia technique for intra-operative and post-operative analgesia for a wide variety of surgeries involving the thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…MAP and HR can reflect the fluctuation in patient’s hemodynamics. Ozen V et al 16 showed that the use of sedative and analgesic drugs and muscle relaxants during thoracoscopic lobectomy was associated with decreased compensatory ability of patients’ circulatory changes, which can lead to the decrease in MAP and HR. Our results confirm this observation.…”
Section: Discussionmentioning
confidence: 99%
“…MAP and HR can reflect the fluctuation in patient’s hemodynamics. Ozen V et al 16 showed that the use of sedative and analgesic drugs and muscle relaxants during thoracoscopic lobectomy was associated with decreased compensatory ability of patients’ circulatory changes, which can lead to the decrease in MAP and HR. Our results confirm this observation.…”
Section: Discussionmentioning
confidence: 99%
“…The first published case of VATS lobectomy under awake epidural anesthesia in Turkey was presented in 2021 by Özen et al [18]. Right upper lobectomy with two ports was successfully performed by placing an epidural catheter under the guidance of ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…TPVB provides very good analgesia and reduces the required dosage of opioids without increasing the occurrence of adverse events. [30][31][32] TPVB has a good adverse event profile; hypotension is among the most common side effects. 33 In agreement with these previous findings, the TPVB+GA group consumed less propofol, sufentanil, and remifentanil, while the postoperative NRS pain score and the incidence of adverse events (shivering, nausea, and vomiting) were comparable to those in the GA group.…”
mentioning
confidence: 99%